2013
DOI: 10.1111/vcp.12069
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of automated assays for immunoglobulin G, M, and A measurements in dog and cat serum

Abstract: The automated human Ig assays showed adequate precision and accuracy with serum samples from dogs and cats. Also, they were able to discriminate different concentrations of Igs in healthy and diseased animals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…Quantification of immunoglobulins in the dog has largely been restricted to the use of the radial immunodiffusion (RID), ELISA, and automated immunoturbidometric methods; based on current literature, RID appears to be the most commonly used method in veterinary medicine for quantifying the total amount of immunoglobulin . Anecdotally, we observed that the IgA RID kit significantly overestimated immunoglobulin concentrations and had poor diagnostic utility, similar to what has been documented in human medicine .…”
Section: Introductionsupporting
confidence: 56%
“…Quantification of immunoglobulins in the dog has largely been restricted to the use of the radial immunodiffusion (RID), ELISA, and automated immunoturbidometric methods; based on current literature, RID appears to be the most commonly used method in veterinary medicine for quantifying the total amount of immunoglobulin . Anecdotally, we observed that the IgA RID kit significantly overestimated immunoglobulin concentrations and had poor diagnostic utility, similar to what has been documented in human medicine .…”
Section: Introductionsupporting
confidence: 56%
“…Group 2 and Group 3 were evaluated together as Group 2-3 whenever possible, for comparison purposes. Moreover, for a subgroup of dogs (10/12 of Group 2 and 7/9 of Group 3) IgA (immunoglobulin), IgM, and IgG fractions were quantified, respectively, at T 0– T 100 and T 0– T 250 using the method described by Tvarijonaviciute [ 16 ]. Briefly, commercial kits (Olympus Europe GmbH) were run on an automatic analyzer (Olympus AU600, Olympus Europe GmbH, Hamburg, Germany) following the manufacturer's instruction.…”
Section: Methodsmentioning
confidence: 99%
“…Similar challenges are noted with human RID and immunoturbidometric and immunonephelometric measurements . An automated human immunoturbidometric method has been validated for canine IgG, IgM, and IgA, and feline IgG and IgM . ELISA assays or refractometry have been used in the dog, cat, and horse …”
Section: Methodsmentioning
confidence: 92%